STRATEGI PENGEMBANGAN WISATA ALAM DI WANA WISATA CURUG CITAMBUR KPH CIANJUR - Ida Parida (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
Forest provides enormous and varied benefits to human life, such as enviromental services in the form of tourism services. The tourism potential is quite large, including BKPH Cibarengkok with the tourism potential of citambur waterfall. The exsistence of the Wana Wisata Citambur (WWC) still requires attention for development, especially in attraction, activities, facilities, accesibility and services for both domestic and foreign tourist destination. This study aims to determine how the rating based on visitor ratings of tourist attraction, facilities, accessibility and services. How is the position of the citambur waterfall tourism area in the SWOT quadrant, and knowing how the strategies that must be applied in the citambur waterfall tourism area. Types of data consist of primary data obtained through observation, questionnaires and interviews. While secondary data comes from literature and research reports. The method used is a SWOT analysis, namely the instrument used to perform a strategy analysis. The results showed that based on the assessment of visitor ratings on attractiveness, facilities, accessibility, and services, some visitors were satisfied with a percentage of 47%. Based on the results of the analysis on the SWOT quadrant, the citambur waterfall tourism object is in quadrant two, namely between the strength and threat (ST) strategy. ST strategy (strength and threat) strategy that uses strength and overcomes threats. a) further increase the exsisting attractions and can create new creative attractions so that they can compete with other tourist objects around the citambur waterfall, b) maintaining the conditions of the citambur waterfall tourist attraction, c) optimizing the natural potential and uniqueness of tourism objects to face tourism object competition.